Event bidding : politics, persuasion and resistance - McGillivray, David; Turner, Daniel (London : Routledge, 2018)
"Bidding contests for sporting and cultural events are attracting increasing media and public attention. Yet, despite the cost, size and scale of these bidding contests, relatively little academic attention has been paid to the strategies and tactics used to develop successful bids. Event Bidding: Politics, Persuasion and Resistance develops a comprehensive, critical understanding of the bidding processes surrounding the award of major peripatetic events. This is achieved by drawing together existing knowledge on the subject of event bidding, combining this with historical and contemporary examples to enable a critical commentary on the bidding process itself and the struggle for power that it represents.The text draws on case studies of 'mega events' including the FIFA World Cup and the Olympic Games as well as a range of smaller peripatetic events from across the world to analyse the bidding process and some of the increasingly controversial issues which emerge during often lengthy and expensive bid campaigns. Finally, the text reflects on a range of critical issues of contemporary significance in bidding contests, including the growing ethical and governance issues surrounding the development and award of events as well as the impact of growing oppositional movements surrounding each contest.This timely volume brings theory and practice together in one place to produce a critical appraisal of a phenomenon with a relatively recent history and is particularly suitable for students, researchers and academics of sports, events, tourism and related subject fields focusing on the strategic and political dimensions of major events."--Provided by publisher.
part, I Politics: contexts and concepts -- chapter 1 Introduction / David McGillivray Daniel Turner -- chapter 2 A history of bidding / David McGillivray Daniel Turner -- chapter 3 Motivations to bid / David McGillivray Daniel Turner -- part, II Persuasion: competencies and campaigns -- chapter 4 Bidding infrastructure -- Demonstrating technical competency / David McGillivray Daniel Turner -- chapter 5 Bidding narratives -- Positioning through storytelling / David McGillivray Daniel Turner -- chapter 6 Bidding tactics -- Campaigning and lobbying / David McGillivray Daniel Turner -- part, III Resistance: corruption and contestation -- chapter 7 Governance, ethics and impropriety / David McGillivray Daniel Turner -- chapter 8 Resistance and alternative campaigns / David McGillivray Daniel Turner -- part, IV Case studies in event bidding -- chapter 9 Rio$1 (Bs 2016 Olympic bid -- s Putting South America on the map / David McGillivray Daniel Turner -- chapter 10 Marseille-Provence 2013 -- r
Keywords: Special events -- Management; Special events -- Planning